Characterisation of native Dagestan grape cultivars using SSR-analysis and the main ampelographic features of the leaves - E. T. Ilnitskaya (Vavilovskij Žurnal Genetiki i Selekcii, 2017)
Local, ancient grape cultivars of different cultivation regions are important part of grapevine genetic resources. Dagestan is one of the oldest regions of viticulture in the Russian Federation. Some Dagestan aboriginal grape varieties are cultivated on an industrial scale, while others are found in single numbers. The study of the native gene pool is given special attention in all grapes producing countries of the world. Currently, the most informative method of plant genotypes analysis is the study at the DNA level. The main features of the leaves of grape varieties are a key ampelographical characteristic. We studied cultivars Agadai, Alyi terskyi, Bor kara, Buday shuli, Gok ala, Gok izyum, Mahbor cibil, Yai izyum beliy, Yai izyum rozovyi by using these approaches. DNA profiles of 9 local Dagestan grape cultivars were obtained on microsatellite loci VVMD5, VVMD7, VVMD27, VVS2, VrZAG62 and VrZAG79 using an automated genetic analyzer ABI Prism 3130. The SSR-markers are recommended as the main for Vitis vinifera L. genotyping. The cultivars analyzed have different sets of allele combination by the loci studied. Evaluation of the genetic similarity of cultivars according to the results of microsatellite analysis showed that the genotypes of Mahbоr cibil and Aliy terskiy are closer to the Western European gene pool of V. vinifera L. than any other native varieties in the sample studied. In addition, the grapevine cultivars studied were described for the main features of the formed leaves according to the method of the international organization of vine and wine. The similarity of cultivars Gok Ala and Agadai was shown by the results of analysis of the leaves characteristics and according to SSR-profiling.